Evaluation method for the physical parameter evolutions of highway subgrade soil using electrical measurements. (20th January 2020) - Yuan, Ganglie; Che, Ailan; Feng, Shaokong
Highlights: The laboratory soil electrical measuring method is presented. The relationship among electrical parameters, water content and compaction degree is obtained. Water content and resistivity of subgrade soil are measured by model test. An analysis method for resistivity data based on normal distribution model is proposed. Abstract: As an important component that bears the upper load, subgrade soil is affected by vehicle load and the natural environment (e.g., dry–wet and freeze–thaw cycles), which deteriorate its performance accordingly. Under repeated and long-term loads, the moisture in subgrade soil migrates, which changes its moisture content. This affects its corresponding mechanical properties, thereby causing large deformations and stability problems. To evaluate the evolution of the physical parameters of subgrade soil (moisture content and compaction degree), electrical measurements were conducted in this study. In addition, to determine the relationship between the electrical and physical parameters of subgrade soil, an electrical measuring device for laboratory soil was developed based on the Wenner four-electrode configuration. Linear and nonlinear fittings were applied to determine the relationships between the electrical parameters, water content, and compaction degree of homogeneous soil. According to the results, the resistivity, water content, and compaction degree share an exponential relationship and the polarizability, water content, and compaction degree share a logarithmic relationship. To evaluate the applicability of the electrical measurement method for the evolution of the physical parameters of highway subgrade soil, an in-situ model test was conducted to measure the distribution of moisture content through a high-density electrical method. A control device for the moisture content in the subgrade was designed, and three moisture content states were prepared. According to the resistivity profile inverted using the high-density resistivity method, the resistivity distribution has many scatter points owing to the inhomogeneity of the subgrade soil materials. The resistivity distribution of homogeneous soil can be obtained by removing the high resistivity caused by coarse granular materials and the low resistivity caused by the moisture between the macropores and using the normal distribution model. Consequently, combined with laboratory experiments, the water content distribution of subgrade soil can be obtained. These results are in agreement with the moisture content test results. Thus, the electrical measurement method can be applied to evaluate the evolution of the physical parameters of highway subgrade soil.